Morpho-Physiological and Molecular Characterization of Maize (Zea Mays L.) Genotypes for Drought Tolerance - Yadav, Pramod Kumar; Singh, A. K.; Tripathi, M. K.; Tiwari, Sushma; Yadav, Sanjeev Kumar; Tripathi, Niraj (European Journal of Applied Sciences, 2022)
Maize is abstemiously sensitive to drought. Drought distresses almost all characteristics of maize growth in variable degrees at all phases of life cycle. Drought pressure, predominantly at flowering period, has been recognized as the most destructing aspect restraining maize production and productivity. So, improving drought tolerance has become the top priority in maize improvement programs. In the current study, 80 genotypes of maize including 66 hybrid, 12 parents and 2 check (drought tolerant HKI1105 and drought susceptible HKI1128 respectively) were included. These genotypes grown under irrigated and partial irrigated conditions and laid out in a randomized block design with two replications. Under irrigated condition, grain yield ranged between 36.29g to 129.6g with a mean value of 73.06g. Whereas under partial irrigated condition, grain yield arrayed between 23.6g to 155.58g with an average worth of 66.11g. Under partial irrigated conditions correlation studies of grain yield displayed significant and positive correlation with relative water contents (RWC) and membrane stability index (MSI) while negative correlation was detected with turgid weight (TW) and saturation water deficit (SWD). Furthermore, molecular characterization also performed employing 20 droughts linked polymorphic microsatellite markers. A total of 110 alleles with a mean of 5.5 alleles per marker were amplified. Cluster analysis revealed that genotypes HKI1105 fallen in a group with 47 other genotypes, so possibility exist that all the genotypes may be drought tolerant. Drought tolerant genotypes and polymorphic microsatellite markers may be further validated and potentially employed in molecular marker-aided breeding to develop drought tolerant cultivar in maize.